Acculturation in Knowledge Intensive Banking: Multi-Dimensional Consequences for Employee Vitality in Job Demands Resource Perspective - Savita Kumari (International Journal of Engineering and Management Research, 2024)
As the industry is getting revolutionized, the knowledge and information is bound to play a central and critical role in shaping the organizational competitiveness and ability to be agile and resilient. The employee based acculturation, getting accustomed to new ways of working, employee based indulgence in open innovation and employee based leverage of social media; seems to count in improving and shaping the employee based productivity in banking perspective. The research seeks to empirically ascertain the relationship between acculturation of employees and employee vitality in rural branches and relies on pre validated scales for construct operationalization. The sample of 309 respondents was leveraged and research hypothesis were found to be true.